2022
DOI: 10.12669/pjms.38.8.6786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma combined with tranexamic acid in the treatment of melasma and its effect on the serum levels of vascular endothelial growth factor, endothelin-1 and melatonin

Abstract: Objective: To investigate the effect of platelet-rich plasma (PRP) combined with tranexamic acid (TXA) in the treatment of melasma and its effect on the serum levels of vascular endothelial growth factor (VEGF), endothelin-1 (ET-1) and melanin stimulating hormone (MSH). Methods: We retrospectively analyzed clinical data of 80 patients with melasma treated in our hospital from January 2020 to June 2021. Patients (n=38) in the control group received simple oral TXA treatment. Patients (n=42) in the study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…In a study by Zhang et al, who investigated the effect of platelet-rich plasma (PRP) combined with tranexamic acid (TXA) in the treatment of melasma and its effect on the serum levels of vascular endothelial growth factor (VEGF), endothelin-1 (ET-1), and melanin-stimulating hormone (MSH), they reported that PRP combined with TXA can improve the treatment outcome, maintaining normal levels of VEGF, ET-1 and MSH, and reducing the recurrence rate [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Zhang et al, who investigated the effect of platelet-rich plasma (PRP) combined with tranexamic acid (TXA) in the treatment of melasma and its effect on the serum levels of vascular endothelial growth factor (VEGF), endothelin-1 (ET-1), and melanin-stimulating hormone (MSH), they reported that PRP combined with TXA can improve the treatment outcome, maintaining normal levels of VEGF, ET-1 and MSH, and reducing the recurrence rate [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 In a study by Zhang et al, who investigated the effect of platelet-rich plasma combined with tranexamic acid (Tranexamic acid) in the treatment of melasma and its effect on the serum levels of vascular endothelial growth factor (VEGF), endothelin-1 (ET-1), and melanin-stimulating hormone (MSH), they reported that PRP combined with Tranexamic acid can improve the treatment outcome, maintaining normal levels of VEGF, ET-1 and MSH, and reducing the recurrence rate. 25 Due of its autologous nature, PRP therapy has a higher safety profile. A further benefit is the abundance of growth factors which facilitate a number of mechanisms that result in facial rejuvenation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Therefore, anti-VEGF drugs have emerged as potential agents to improve the therapeutic effect of DME. 7,8 Ranibizumab is a second-generation humanized recombinant monoclonal antibody fragment against VEGF, which can selectively bind to VEGF and inhibit endothelial cell proliferation, thereby exerting therapeutic effects. 9,10 Several studies have suggested the superiority of combining laser treatment with anti-VEGF therapy in patients with DME.…”
Section: Introductionmentioning
confidence: 99%